Repose : An Exhibition of Better Folding Chairs. - Bellerby, Greg; David, Henry; Shotton, Elizabeth (Vancouver : Charles H. Scott Gallery, 1998)
Woodruff, Matthew ; Wall, Peter ; Thomas, Craig ; Matusevics, Anita ; Halter, Jason ; Bartman, Daniel ; Boszko, Orest ; Verity, Mike ; Plain, Robert ; Braithwaite, Jed ; Lasnier, Louis-Charles ; Israelsson, Pia ; Kemp, Scott ; Cuddington, Clint ; Gulay, Louise Bedard & Donald ; Peter, Martin ; Suchy, Steve ; Cardew, Peter
Engels
boek